Towards fair and low latency next generation high speed networks: AFCD queuing. (July 2016) - Xue, Lin; Kumar, Suman; Cui, Cheng; Kondikoppa, Praveenkumar; Chiu, Chui-Hui; Park, Seung-Jong
Abstract: In packet switched high-speed networks, heterogeneous nature of TCP flows, a relatively newer characteristics of IP networks, and high burstiness have made it difficult to achieve low queuing delay and fair allocation of bandwidth among flows. Existing queue management (QM) schemes were designed to achieve either one or the other or both simultaneously and have been fairly successful at meeting either fairness or low queuing delay but not both at the same time. In this paper, unlike previous research efforts, the two requirements, fairness and low queuing delay are decoupled and addressed separately. We propose Approximated-Fair and Controlled-Delay (AFCD) queuing for next generation high speed networks that aims to meet following design goals: approximated fairness, controlled low queuing delay, high link utilization and simple implementation. The design of AFCD utilizes a novel synergistic approach by forming an alliance between approximated fair queuing and controlled delay queuing. It uses very small amount of state information in sending rate estimation of flows and makes drop decision based on a target delay of individual flow. Through experimental evaluation in a 10 Gbps high speed networking environment, we show AFCD meets our design goals by maintaining approximated fair share of bandwidth among flows and ensuring a controlled very low queuing delay with a comparable link utilization. AFCD is locally stable for small target delay in a high speed networking environment.